Results in the characterization of the repetition rate of conventional radiographic imaging in a pediatric hospital - Niño Torres, Carlos Fernando
Talking about conventional radiology refers to diagnostic images obtained by ionizing radiation,, which can be visualized on radiographic films or high resolution consoles. These images must comply with high radiographic quality standards so that the radiologist can make a timely and accurate diagnosis. In pediatric patients, when acquiring images, it is essential to observe greater rigor in order to avoid repeating any study. Since children are very young, they have a greater number of immature and proliferating cells, which makes them more sensitive to ionizing radiation and more likely to present late side effects throughout their lives. For this reason, radiological protection is important in this population and the repetition of radiographic images should be carefully reviewed to avoid irreparable damage. The purpose of this research was to characterize the causes of recurrence of radiographic images taken in pediatric patients in a Health Care Institution in Bogotá, through a detailed analysis of the causes of recurrence. In a radiology service that seeks to provide health services with quality assurance, it is necessary to consider that its purpose is to produce radiographic images of optimum quality without unnecessarily affecting the patient and keeping them at the lowest possible cost. Therefore, it is important to mention that, in the implementation of the quality assurance program in radiodiagnostic, it is essential to begin with the evaluation of radiographic images that are repeated because they do not have the necessary quality for diagnosis, establishing in detail their causes and percentages.